Deterioration rate of renewable polyurethanes composites prior to ultra violet irradiation exposure - M. Rus, Anika Zafiah; Abdullah, Nur Munirah (Elsevier, 2019)
Polyurethanes (PU's) made from renewable and sustainable materials are one of the most important groups of polymers because of their versatility with wide range of grades, densities and stiffness. In this project, polymers based on renewable materials such as rapeseed (RS) and sunflower oil (SF) were synthesized and cross-linked to form polyurethanes. The effect of prolonged exposure up to 1000 h upon UVB light, in general promotes photodegradation for both RS and SF-based polyurethanes, both neat and also composites loaded with TiO2. The addition of 10% Degussa P25 TiO2 pigment, gives the greater degradation while PUs loaded with 5% Kronos 2220 show the slowest rates of degradation due to the effect of the coating of this pigment. The photostabiliser Tinuvin 770 offers high protection from UVB, thus lead the combination of Tinuvin 770 with Degussa P25 promotes the highest protection from UVB exposure. Moreover, addition of Tinuvin 770 at the stage of preparation of the PUs also greatly reduced the undesirable yellow colouration prevalent during PU synthesis.